Simplified partial resampling method for state estimation usingparticle filter - Tirumala Reddy, M; Sri Ganesh, Y; Lakshmi Gayathri, Ch; Megha Shyam, T; Koteswar Rao, S; Gopi Tilak, V (International Journal of Engineering and Technology, 2018)
Particle filter methods are used in the estimation and tracking of the objects for non-linear and non-gaussian noise conditions. In this paper work the object estimation using partial resampling methods are discussed. On using partial resampling method resampling becomes faster. The performance of particle filter with partial resampling scheme is analyzed using the state estima-tion of a simple pendulum.